PRINCIPAL MODELAS AS A PART OF SEISMIC DATA INTERPRETATION - Tsybulskyi, V.; Trypilskiy, O.; Kuzmenko, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A conceptual model of the Lower Maykopian sediments for Subbotina field within the Kerch shelf of the Black Sea was proposed. These ideas used in deterministic and stochastic calculation process of effective filtration and capacity models. The effect of fracturing was considered in case of hydrocarbon deposits formation.